NEW LEAN the modern approach to continuous improvement. - Toppazzini, Kyle. ([S.l.] : PRODUCTIVITY PRESS, 2024)
In today's rapidly changing business landscape, organizations are challenged not only to adapt to evolving market dynamics but to excel in the face of uncertainty. Continuous improvement emerges as a strategic imperative, offering a systematic approach to enhance processes, boost efficiency, and drive innovation. This book delves into the heart of continuous improvement, providing a roadmap for organizations to navigate their journey toward maturity. The continuous improvement maturity model (CIMM) described in this book is not just a framework, but a holistic guide designed to support organizations in assessing and advancing their continuous improvement capabilities. As the author embarks on this exploration, he presents an approach that spans from foundational practices to advanced strategies. CIMM is a versatile tool adaptable to diverse industries, sectors, and organizational sizes. The key components of CIMM are: Integration with Best Practices--CIMM is not designed in isolation. We highlight its compatibility with established continuous improvement methodologies such as Lean, Six Sigma, Change Management, and Leadership Attributes. Learn how to leverage existing best practices while embracing the unique contributions of CIMM. Practical Application--Real-world examples and practical insights illustrate how organizations have successfully applied CIMM to overcome challenges, drive innovation, and achieve sustainable excellence. These stories offer inspiration and guidance for your own journey.
Keywords: Continuous improvement process; Organizational change; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Quality Control